2014
DOI: 10.1111/nure.12111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary macronutrient distribution on BMI and cardiometabolic outcomes in overweight and obese children and adolescents: a systematic review

Abstract: The present systematic review examined the effectiveness of weight management interventions comparing diets with varying macronutrient distributions on BMI and cardiometabolic risk factors in overweight or obese children and adolescents. A systematic search of seven databases for the period 1975-2013 identified 14 eligible randomized or quasi-randomized controlled trials conducted with 6-18-year-old subjects. Seven trials compared a low-fat (≤ 33% energy or < 40 g/day) to an isocaloric (n = 2) or ad libitum (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(90 citation statements)
references
References 59 publications
(242 reference statements)
3
84
0
3
Order By: Relevance
“…Our 2014 systematic review with meta-analysis examined, for the first time, whether variations in dietary macronutrient content differentially affect changes in weight and cardio-metabolic risk factors in children and adolescents who are overweight or obese [12]. Overall, the review indicated improved weight status in children and adolescents undergoing obesity treatment, irrespective of the macronutrient distribution of a reduced-energy diet.…”
Section: Macronutrient Distribution Of the Diet And Weight Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Our 2014 systematic review with meta-analysis examined, for the first time, whether variations in dietary macronutrient content differentially affect changes in weight and cardio-metabolic risk factors in children and adolescents who are overweight or obese [12]. Overall, the review indicated improved weight status in children and adolescents undergoing obesity treatment, irrespective of the macronutrient distribution of a reduced-energy diet.…”
Section: Macronutrient Distribution Of the Diet And Weight Lossmentioning
confidence: 99%
“…While there may not be an impact on weight loss, findings from our 2014 systematic review did suggest the potential for the specific application of certain macronutrient distributions to target certain T2DM risk factors [12]. …”
Section: Macronutrient Distribution Of the Diet And Improvements Imentioning
confidence: 99%
“…Further, consumption of whole fruits, vegetables and dietary fiber is encouraged in addition to portion control education, enhancing food labeling, and encouraging eating regular meals to avoid grazing (47). A recent meta-analysis conducted by Gow et al (55) suggests that primary goal in dietary intervention programs should focus on reduced total energy intake based on the observation that a reduced energy diet, irrespective of the macronutrient distribution, was successful in improving weight status in overweight and obese children and adolescents. It is essential that dietary interventions and calorie reduction in children and adolescents are supervised by an experienced dietician in growing children's needs (47).…”
Section: Dietary Interventionmentioning
confidence: 99%
“…Indeed, higher-calorie fattier foods and higher-fat diets may produce and sustain as much or more weight loss than calorie-restricted or higher-carbohydrate diets (9,10,89-98) -particularly among those already having metabolic abnormalities (93,94,99) . Moreover, certain fattier/lower-carbohydrate diets may also be associated with favourable metabolic indicators (10,89,(91)(92)(93)(94)(98)(99)(100)(101)(102)(103)(104)(105)(106)(107)(108)(109) , reduced adverse health events (69,102,110,111) and delayed mortality (110)(111)(112)(113) .…”
Section: More-nuanced Thinking About Obesity and Related Diseasesmentioning
confidence: 99%